(untitled) (International Journal of Language, Literacy and Translation, 2025)
In recent decades, an increasing number of learners from Kazakhstan have visited China to study Mandarin Chinese. Hence, it is necessary to pay more attention to the acquisition of Mandarin Chinese by Kazakh-speaking learners. The purpose of the present paper is to provide helpful countermeasures for Chinese teaching practice. This study will enrich the achievements of Kazakh and Mandarin first-class vowels comparison and improve the teaching quality of Mandarin Chinese among Kazakh-speaking learners. A total of 14 Kazakh speakers and six Chinese speakers participated in a word-list reading task. For acoustic analysis, we measured the formant frequencies (F1 and F2) through Mini-speech Lab software developed by Nankai University, Tianjin, P.R. China. Results demonstrate that the tongue position of (1) /a/ in the Kazakh language is higher than that in Mandarin Chinese, (2) / ? i u y / in the Kazakh language is lower than that in Mandarin Chinese, (3) / ? u / in the Kazakh language is more fronted than that in Mandarin Chinese, and (4) / a i y / in the Kazakh language is more backward than that in Mandarin Chinese.